Position and Shape of the Mental Foramen in a Coastal Syrian population (Radiographic study by CBCT) - اسكيف, كرم; سميره زريقي , (Latakia University Journal -Medical Sciences Series, 2024)
Aim of the study: This study aimed to evaluate the position and the shape of the mental foramen radiographically by CBCT in a selected Coastal Syrian population, and to study the relation between these variables and individual factors (gender, age and side). Materials and Methods: This Retrospective Radiographic study concluded 200 CBCT scans (104 Female, 96 Male), 400 hemimandibles were evaluated, The individuals were categorized into 3 Age groups: [20-35],[36-50],[51-65] ,CS 3D Imaging software was used to view the CBCT scans, then the statistical analysis was done by IBM SPSS Statistics 25. Results: The most common position of the mental foramen was between the two premolars (52.61% prevalence percentage), followed by the position along the long axis of the second premolar (34.7% prevalence percentage), and the most common shape of the mental foramen was round (59% prevalence percentage), followed by horizontal oval shape (36.5% prevalence percentage). Conclusions: Within the limitations of this study, it can be concluded that the age has an effect on the position of the mental foramen, The gender has no effect on the position and the shape of the mental foramen in the studied population.